The Heart-Brain Connection in Depression: Can it inform a personalised approach for repetitive transcranial magnetic stimulation (rTMS) treatment?. (August 2021) - Michael, Jessica A.; Kaur, Manreena
Abstract: There is growing enthusiasm into the frontal-vagal network theory of major depressive disorder (MDD) and the potential role of a frontal-vagal network in the therapeutic mechanism of repetitive transcranial magnetic stimulation (rTMS) treatment for MDD. A review of the autonomic nervous system (ANS) in MDD and its role in antidepressant treatment for MDD is timely. The literature supports the well-established notion of ANS dysfunction in MDD and the benign effect of selective serotonin reuptake inhibitors, but not tricyclic antidepressants, on perturbed ANS function in MDD. Notwithstanding, there is some evidence that ANS measures have the capacity to inform response to antidepressant medication treatment. While there is a paucity of studies on the effects of rTMS on the ANS, critically, there is preliminary support that rTMS may alleviate ANS dysfunction in MDD and that ANS measures are associated with rTMS treatment response. These observations are consistent with the frontal-vagal theory of depression and the emerging literature on the use of ANS measures for personalising and optimising rTMS treatment of MDD.